Internal auditing : assurance & advisory services / Urton Anderson ...[et al] - Anderson, Urton L.
Written through the collaboration of educators and practitioners, this textbook serves as a cornerstone for internal audit education. It covers key fundamentals of internal auditing that can be applied in an ever-changing business world, serving as a reference and training tool for internal audit practitioners. The textbook is completely aligned to The IIA s Code of Ethics and International Standards for the Professional Practice of Internal Auditing. The fourth edition includes online student and instructor tools that include case studies and leading generalized audit software packages and knowledge content from ACL, CaseWare IDEA, Wolters Kluwer s TeamMate, and Protiviti s KnowledgeLeader®. Supplemental teaching materials are available for instructors upon request. THE FOURTH EDITION HAS BEEN UPDATED TO REFLECT: The latest release of The IIA s International Professional Practices Framework (IPPF) and the Committee of Sponsoring Organizations of the Treadway Commission s (COSO s) exposure draft of the Enterprise Risk Management Aligning Risk with Strategy and Performance Framework. Emerging developments in technology, including a heightened focus on cybersecurity and the impact of associated risks to organizations. The latest information and data from the new COSO Fraud Risk Management Guide and data from the Association of Certified Fraud Examiners (ACFE). A robust discussion of the benefits of using data analytics to provide assurance as part of internal audit activities. Wolters Kluwer s latest version of TeamMate audit management software enhancements with improved case studies in end-of-chapter material as applicable. Protiviti s resource, KnowledgeLeader®, which has been integrated throughout the content in the form of relevant case study material at the end of each chapter, encouraging students to conduct further research and apply critical-thinking skills. Previous editions have been translated into French, Spanish, and Japanese and adopted by many universities around the world. This fourth edition promises to build on the success of this bestseller, significantly contributing to the internal audit profession s body of knowledge and introducing students to the dynamic world of internal auditing.